Reply to comment by Christopher Talbot on "Approach to estimating the maximum depth for glacially induced hydraulic jacking in fractured crystalline rock at Forsmark, Sweden" - Hökmark, H.; Lönnqvist, Margareta (Journal of Geophysical Research: Earth Surface, 2014)
As illustrated in Figure 2 of our paper and as noted in numerous previous studies by Talbot [1990, 1999] and others [e.g., Chan et al., 2005; Vidstrand et al., 2008], the water pressure at the ice-bed interface many kilometers behind the margin of an advancing, stationary, or retreating ice sheet would be sufficient to jack open fractures at depths of several hundred meters in the region around the ice margin. This has raised the question of whether or not hydraulic jacking should count as a potential concern for the nuclear waste repository projected at about 450m depth in Forsmark. However, as explained in our paper, for these high pressures to actually be effective in the region around the ice margin, unrealistic assumptions regarding the fracture network and the background permeability have to be made. The objective of our study and our calculations is to establish more realistic upper bound estimates of the water pressure around the margin, and consequently of the maximum jacking depth, by taking due account of the actual large-scale hydrological conditions in the Forsmark region. The theoretical ice sheet profile assumed in our models has a significantly steeper slope than corresponding profiles of SKB's reference reconstruction of the latest Fennoscandian ice sheet. Its maximum height overestimates the reconstruction maximum height by about 1000mduring advance and by about 500mduring retreat. This, in combination with worst case assumptions regarding ice retreat speed, distance between permafrost melt-zone and ice margin, and last but not least, regarding the extension, homogeneity, and permeability of the proglacial permafrost, is therefore highly likely to have given overestimated water pressures below the margin. We are therefore not "playing down the maximum depth to which this process [hydraulic jacking] can reach by making questionable assumptions" as Talbot [2014] claims. The comment made by Talbot [2014] regarding seasonal variations appears to be based on a misunderstanding. That we are "assuming ...